Effect of chitosan coating enriched with oregano essential oil on the quality of refrigerated meat hamburgers - Amadio, Claudia; Farrando, Silvina; Zimmermann, Mónica (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2019)
Antimicrobial and antioxidant properties of oregano essential oil (OEO) have been extensively reviewed. Its application may adversely impact the sensory perception of food. In this sense, an interesting approach to reduce its dose, while maintaining effectiveness, could be to incorporate these compounds into coatings. To determine the antioxidant and antimicrobial potential of chitosan coatings with OEO in hamburgers stored at 4ºC, 3 batches were elaborated with 1% v/v acetic acid in water (control), pure chitosan (1%), chitosan with addition of 2% OEO. Stability was assessed by radical-scavenging activity (DPPH), thiobarbituric acid reactive substances (TBARS), pH, color, microbiological analysis and sensory evaluation (hedonic scale of 5 points). The addition of OEO to the coating improved the antioxidant property and the red color (a*) of these burgers was always higher. The pH was not significantly affected by treatments. All samples showed similar yeast and fungal counts, while the psychrophilic bacteria increased with the addition of OEO to the coating. Sensorially, the treatment with chitosan + OEO coating obtained the highest score in color and smell, along with the control. Taste and acceptability deteriorated over time. The addition of OEO to the coating of chitosan allowed improving the antioxidant property of chitosan and therefore the color of the hamburgers, while sensorially accepted. There was no evidence of a preservative effect.